Analyzing The Consumer’s Rice Price using Multiple Linear Regression and X-12 ARIMA - Asep Saefuddin; Anang Kurnia; Dian Kusumaningrum (FORUM STATISTIKA DAN KOMPUTASI, 2004)
Rice is one of the main foods in Indonesia. A change of rice price will cause a major effect in the lives of consumers.  On the other hand, there are so many factors that influence the rice price. Thus finding key factors which are significant to the rice price, as well as forecasting the consumer’s rice price are needed in order to maintain the stabilization of rice price. The second objective is to find key factors which influence the rice price by using multiple linear regression models. The parameters were estimated by ordinary least square methods. There are 6 variables that are significant at α=5%, which are the consumer’s rice price at the previous period, rice production at the current and previous period, farmer’s GKP price, realization of domestic stock, and total rice import. The rice price will increase if the GKP price and realization of domestic stock increase whereas total rice import and the consumer’s rice price at the previous period have negative influences towards the rice price. The impact of imported rice is negative towards domestic rice. This condition will also drive negative effect towards the farmer’s income, in this case the price does not meet the farmers cost for production. To protect the farmers, the government applied a 430.00 Rp/Kg imported rice fee but this is not effective to decrease the amount of imported rice.  In this model rice production at the current and previous period have positive signs, contradictory to the microeconomic theory where when the rice production increases, there will be an excess supply and the price will drop. That condition will occur only if the commodity is a free commodity and the rice is at the sufficiency level but in Indonesia, rice is affected by the government’s policy and the rice productivity is left behind by the demand. Forecasting the consumer’s rice price for the next five years was the last objective of this research. ARIMA Box–Jenkins Method, X-12 ARIMA, Winter’s Method, and Trend Analysis were compared to find the best statistical model to forecast the consumer’s rice price. X-12 ARIMA turns out to be the best method because it has the smallest MAPE, MAD, and MSD value. This result is a satisfactory because according to Findley et al. (1998) X-12 ARIMA has the capability to adjust seasonal and trading day factors which usually causes fluctuations in an economic time series data.     Keyword : X-12 ARIMA